PENGARUH KARAKTERISTIK TUJUAN ANGGARAN TERHADAP KINERJA MANAJERIAL DENGAN KOMITMEN ORGANISASI SEBAGAI MODERATING - Aziz, Faizal Umar; Handayani, Nur (Jurnal Ilmu dan Riset Akuntansi (JIRA), 2015)
The purpose of this research is to test the influence of the characteristic of budgetary purposes to the managerial performance and to examine the influence of organizational commitment to the correlation between characteristic of budgetary purposes and the managerial performance either to strengthen or to weaken at the Dinas Kebersihan dan Pertamanan Kota Surabaya. Quantitative method has been applied in this research. The population is all employees who have authority in budget preparation at the Dinas Kebersihan dan Pertamanan Kota Surabaya and the samples are 30 people. The analysis technique has been done by using Moderator Regressions Analysis. The result of the test shows that characteristic of budgetary purposes has positive and significant influence to the managerial performance. The following result of the research shows that the interaction of coefficient Î² is significant and it shows that the organization commitment is the moderator variable between characteristic of budgetary purposes and the managerial performance. It indicates that the positive influence from characteristic of budgetary purposes to the managerial performance is very high when the organization commitment is high as well.Keywords: The Characteristic of Budgetary Purposes, Organization Comitment, Managerial Performance.